2012
DOI: 10.1590/s0100-40422012000300015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of geranylhydroquinone derivatives with potencial cytotoxic activity

Abstract: Recebido em 12/5/11; aceito em 29/8/11; publicado na web em 26/9/11 Natural geranylhydroquinone 1 and geranyl-p-methoxyphenol 2 were prepared by Electrophilic Aromatic Substitution (EAS) reactions between geraniol and 1,4-hydroquinone or p-methoxyphenol respectively, using BF 3 •Et 2 O as a catalyst. Furthermore, natural geranylquinone 3, geranyl-1,4-dimethoxyquinone 4 and the new geranyl-4-methoxyphenyl acetate 5 were obtained by chemical transformations of 1 and 2. The compounds were evaluated for their in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 7 publications
5
27
0
Order By: Relevance
“…The direct coupling between geraniol and commercially available 4-methoxyphenol using acetonitrile/AgNO 3 gives compound 6 as a unique product with 18% yield, which is almost twice the yield reported for the same reaction in dioxane (10%) [ 15 ]. However, this yield is much lower than that reported for the reaction of 4-methoxyphenol with geranyl bromide in the presence of NaH, which leads to 6 with a 56% yield [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The direct coupling between geraniol and commercially available 4-methoxyphenol using acetonitrile/AgNO 3 gives compound 6 as a unique product with 18% yield, which is almost twice the yield reported for the same reaction in dioxane (10%) [ 15 ]. However, this yield is much lower than that reported for the reaction of 4-methoxyphenol with geranyl bromide in the presence of NaH, which leads to 6 with a 56% yield [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our first objective was the preparation of compounds 2, 4-5, using the coupling method previously described by us [18,19] with geraniol and commercially available hydroquinone and orcinol, respectively. In this case, 2-geranylhydroquinone 2 was obtained with 28 % yield, whereas the compounds 4 and 5 were obtained with 12.6 % and 27.6 % yields, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of compound 13 (geranylphloroglucinol proposed name by us in analogy with the name of geranylorcinol) was development by direct geranylation reactions between phloroglucinol (benzene-1,3,5-triol) and geraniol with a 4,2 % yield. Later, the compound 13 was methylated with dimethylsulfate in acetone as was previously described by us for other compounds [18]. The trimethoxylated derivative 14 was obtained with a 98.5 % yield.These reactions are shown in scheme 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…activity was found for 2-geranylbenzoquinone and 2-geranylhydroquinone, and some synthetic geranylphenol-geranylmethoxy derivatives were also described as cytotoxic [27][28][29][30][31] . Another interesting study reported the anticancer activity and probable mechanism of action of 3-demetylubiquinone Q2 32 .…”
Section: Cytotoxicmentioning
confidence: 99%